2007
DOI: 10.1007/s10661-006-9522-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal Pollution Assessment of Surface Sediments Along a New Gas Pipeline in the Niger Delta (Nigeria)

Abstract: Chromium, nickel, copper, zinc and cadmium were determined in sediments of the Niger Delta (Nigeria) in order to discriminate between natural metal sources and anthropogenic ones. Surface sediments were collected at seven sites along a new gas pipeline near Port Harcourt, between the New Calabar River and the Bonny River towards Bonny town. Chemical characterisation is obtained by hydrofluoric-nitric acid digestion procedure, providing the 'total' ('residual') metal contents. Information about the anthropogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Against the total sewage generation of 195 MLD, Srinagar has four sewage treatment plants with a total capacity of 32.2 MLD (Farhat, 2006). Studies have shown that sewage treatment processes might also affect the Physicochemical parameters of the final effluent such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), electrical conductivity, total hardness, alkalinity, dissolved oxygen, some metals, and non-metal ions (Rawat et al,1998;Adami et al, 2007). In addition, purification processes remove pathogenic microorganisms (Reasoner, 1982;Wang et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Against the total sewage generation of 195 MLD, Srinagar has four sewage treatment plants with a total capacity of 32.2 MLD (Farhat, 2006). Studies have shown that sewage treatment processes might also affect the Physicochemical parameters of the final effluent such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), electrical conductivity, total hardness, alkalinity, dissolved oxygen, some metals, and non-metal ions (Rawat et al,1998;Adami et al, 2007). In addition, purification processes remove pathogenic microorganisms (Reasoner, 1982;Wang et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies determining the concentration of zinc in sediment samples have been reported; these have used sample solutions prepared mainly by acid digestion [8][9][10]. However, the preparation of sample solutions is time consuming and has a multistep procedure, which makes it difficult to analyse large numbers of sediment samples; e.g.…”
Section: Introductionmentioning
confidence: 99%